2014
DOI: 10.1007/s12155-014-9490-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate Impact of Willow Grown for Bioenergy in Sweden

Abstract: Short rotation coppice willow (SRCW) is a fast-growing and potentially high-yielding energy crop. Transition to bioenergy has been identified in Sweden as one strategy to mitigate climate change and decrease the current dependency on fossil fuel. In this study, life cycle assessment was used to evaluate and compare the climate impacts of SRCW systems, for the purpose to evaluate key factors influencing the climate change mitigation potential of SRCW grown on agricultural land in Sweden. Seven different scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…There are still uncertainties about which further factors control the N 2 O emission within perennial crops. As reported for CH 4 [55], soil moisture may also play a role in the emission of N 2 O in energy crops, which however was not the focus of this study. But it could be shown that N 2 O emissions were positively influenced by the number of weeks after planting in the 1st rotation period and harvesting in the 2nd and 3rd rotation periods, respectively.…”
Section: Driving Forces Of Ghg Emissions In Srcmentioning
confidence: 81%
See 2 more Smart Citations
“…There are still uncertainties about which further factors control the N 2 O emission within perennial crops. As reported for CH 4 [55], soil moisture may also play a role in the emission of N 2 O in energy crops, which however was not the focus of this study. But it could be shown that N 2 O emissions were positively influenced by the number of weeks after planting in the 1st rotation period and harvesting in the 2nd and 3rd rotation periods, respectively.…”
Section: Driving Forces Of Ghg Emissions In Srcmentioning
confidence: 81%
“…In spring and autumn, five soil cores (volumetric sampling) were taken from each subplot and analysed for pH, C t , total nitrogen (N t ), and the extractable potassium (K CAL ), phosphorus (P CAL ) and nitrogen (N min ) in the soil layers 0-30 cm and 30-60 cm. N min (NH 4 + and NO 3 − ) was extracted from 50 g fresh soil in 200 ml of 0.0125 M CaCl 2 . Ammonium and NO 3 − from the extracts were measured colorimetrically using the CFA SAN-SYSTEM (Skalar).…”
Section: Soil Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the changes in soil organic carbon (SOC) and the CO 2 fluxes between soil, biomass and atmosphere have been shown to highly influence the result [23,20,[24][25][26][27]. To model the forest carbon balance, process-based models were used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, SRICs of willows could partly replace the use of fossil fuel for heat production. Short-rotation intensive cultures of willows also display a high potential to accumulate carbon (C) in soil, thereby offsetting the use of fossil fuel and greenhouse gas emissions [7,8]. Studies that investigated the potential of SRICs of willows to accumulate soil C in the form of organic matter (OM) have resulted with contradictory results.…”
Section: Introductionmentioning
confidence: 99%